Multi-shot gradient-echo planar imaging sequence in non-contrast coronary magnetic resonance angiography - Zhu, Jiajia; Li, Wenjing; Lu, Guangming; Jin, Dongsheng; Hu, Qiuju; Yuan, Yong; Luo, Song; Zhao, Yane (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo explore the feasibility of multi-shot gradient-echo planar imaging (MSG-EPI) sequence in non-enhanced coronary artery magnetic resonance angiography (CMRA).MethodsPatients undergoing CMRA in the Geriatric Hospital of Nanjing Medical University from November 2023 to May 2024 were included. We compared MSG-EPI and three-dimensional balanced turbo field echo (3D BTFE) sequence in acquisition time, subjective image score, signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR). With CTA as the reference standard, the linear weighted kappa and compared chi-square Mcnemar test were used to evaluate the diagnostic efficacy of both sequences for coronary artery diseases (CADs). The scale for the kappa coefficients was interpreted as follows: <0.2 = poor, 0.2–0.4 = fair, 0.4–0.6 = moderate, 0.6–0.8 = substantial, and >0.8 = excellent.ResultSeventy-two patients (33 males; mean age 54.5 ± 14.7 years old, range from 18 to 79 years old) were enrolled. MSG-EPI had a significantly shorter acquisition time than 3D BTFE (17.21 ± 1.08 s vs. 558.10 ± 102.90 s, P < 0.001). No significant differences in subjective scores were found between sequences for the proximal and middle segment of RCA, LM, the proximal segment of LAD and LCX (P = 0.168, 0.097, 0.126, 0.065, 0.062, respectively). SNR evaluations revealed no significant differences in the proximal and middle segment of RCA and LM segment (P = 0.119, 0.105, 0.237, respectively). However, in coronary artery segment analysis, the CNR was significantly higher in 3D BTFE compared to MSG-EPI (P all <0.05). The kappa values for MSG-EPI and 3D BTFE in assessing stenosis were 0.785 and 0.814, respectively. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of MSG-EPI were 86.7%, 83.3%, 76.5%, 90.9%, and 84.6%, respectively. The area under the curve (AUC) of MSF-EPI and 3D BTFE for CADs diagnosis was 0.850 (0.699–0.944) and 0.879 (0.735–0.961), respectively (P = 0.543).ConclusionMSG-EPI sequence could significantly shorten the acquisition time and provide sufficient image quality for CADs evaluation in non-enhanced CMRA.